Program dan Akvitivi Dakwah Muhammadiyah Masakini - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1997)
The article discusses the activities of Muhammadiyah, the main and the most advanced da’wah organisation in Indonesia. The activities of Muhammadiyah covers almost all aspects of human life. The study reveals that the da’wah of the organisation is based on the broad meaning of da’wah, i.e. to be involved in all human activities for the betterment of life.